Comparative study of PVD and CVD cutting tools performance in milling of duplex stainless steel - Martinho, R. P. (2019)
The machining process evolution has been accompanied by the improvement of tool performance, being this mainly due to the development of thin coatings, mono and multi-layered, providing the most appropriate set of properties for each machining condition. On the other hand, duplex stainless steels have registered a strong increase in demand, which, in many cases, requires the use of machining processes in order to obtain the final shape accurately. Taking into account these two aspects, this paper aims essentially to evaluate the performance of two cutting inserts with PVD and CVD coatings, used in rough milling operations of duplex stainless steel. The cutting parameters and machining conditions were those recommended by the manufacturer and were kept unchanged in all performed tests. The behavior of the PVD- and CVD-coated cutting tools was assessed using three different facets: (a) surface roughness analysis, (b) tool wear evaluation, and (c) the monitoring of vibration levels produced during each test. CVD (TiN/TiCN/Al2O3)-coated inserts showed very good suitability to be used as tools for roughing milling operations when machining super duplex stainless steels.